MEG3 Alleviated LPS-Induced Intestinal Injury in Sepsis by Modulating miR-129-5p and Surfactant Protein D - Xianjin Du; Dan Tian; Jie Wei; Chen Yan; Peng Hu; Xu Wu; Wenbin Yang (Mediators of Inflammation)
Sepsis and intestinal injury triggered by sepsis are common in intensive care units, which can contribute to a high mortality. lncRNAs can modulate gene expression, and they are closely involved in multiple diseases, including sepsis. In our present study, we investigated the biological function of MEG3 in sepsis, especially during the intestinal injury. Currently, we observed that in LPS-induced sepsis mouse models, the intestinal injury was triggered. Meanwhile, we reported that MEG3 was greatly decreased in vivo, with an increase of miR-129-5p and inhibition of SP-D. Then, MEG3 was overexpressed, and we found that its overexpression repressed the intestinal injury via downregulating miR-129-5p in sepsis mice. Moreover, TNF-α and IL-6 expression was elevated in intestinal tissues compared to the control groups. MEG3 restrained the activation of TNF-α and IL-6, in sepsis models. Subsequently, to induce the inflammatory injury of sepsis, human colorectal Caco2 cells were treated with 10 ng/ml LPS. 10 ng/ml LPS significantly inhibited Caco2 cell proliferation and increased the apoptosis. Additionally, MEG3 was decreased whereas miR-129-5p was obviously increased in Caco2 cells incubated with LPS. Interestingly, we showed that MEG3 repressed cell apoptosis partly and enhanced Caco2 cell proliferation. miR-129-5p overexpression could reverse the effect of MEG3 in vitro. Previously, we proved SP-D was reduced in sepsis and it depressed the intestinal injury in vivo. Finally, the correlation among MEG3, miR-129-5p, and SP-D was predicted and confirmed in our investigation. These findings indicated that MEG3 might be a potential target for intestinal damage caused by sepsis via regulating miR-129-5p and SP-D.